Analisis Kesulitan Merancang ERD Mata Kuliah Basis Data pada Mahasiswa Program Studi Pendidikan Matematika IKIP Budi Utomo Malang - Rachmawati Rachma (JICTE (Journal of Information and Computer Technology Education), 2017)
This study aims to describe the types and causes of student error IKIP Budi Utomo Malang in designing ERD (Entity Relationalship Diagram) in the course Database. The research method used in this research is descriptive qualitative. Instrument of data collection in this research include: (1) test of case study used to know the location of student error in designing ERD. (2) interviews to students who are used to obtain data causes factor error. Based on the results of errors in designing ERD conducted by IKIP Budi Utomo Malang students are conceptual error for case study one as much as 34%, case study two as much as 24%. The procedural error for case study 1 is 27% and case study two is 31%. Technical error case study one does not exist, while case study two is 0.25%.